Liver growth prediction in ALPPS – A multicenter analysis from the international ALPPS registry. (26th May 2022) - Lopez‐Lopez, Victor; Linecker, Michael; Cruz, Juan; Brusadin, Roberto; Lopez‐Conesa, Asuncion; Machado, Marcel Autran; Hernandez‐Alejandro, Roberto; Voskanyan, Alejandro Sergey; Li, Jun; Balci, Deniz; Adam, René; Ardiles, Victoria; et al.
Abstract: Background: While ALPPS triggers a fast liver hypertrophy, it is still unclear which factors matter most to achieve accelerated hypertrophy within a short period of time. The aim of the study was to identify patient‐intrinsic factors related to the growth of the future liver remnant (FLR). Methods: This cohort study is composed of data derived from the International ALPPS Registry from November 2011 and October 2018. We analyse the influence of demographic, tumour type and perioperative data on the growth of the FLR. The volume of the FLR was calculated in millilitre and percentage using computed‐tomography (CT) scans before and after stage 1, both according to Vauthey formula. Results: A total of 734 patients were included from 99 centres. The median sFLR at stage 1 and stage 2 was 0.23 (IQR, 0.18–0.28) and 0.39 (IQR: 0.31–0.46), respectively. The variables associated with a lower increase from sFLR1 to sFLR2 were age˃68 years (p = .02), height ˃1.76 m (p ˂ .01), weight ˃83 kg (p ˂ .01), BMI˃28 (p ˂ .01), male gender (p ˂ .01), antihypertensive therapy (p ˂ .01), operation time ˃370 minutes (p ˂ .01) and hospital stay˃14 days (p ˂ .01). The time required to reach sufficient volume for stage 2, male gender accounts 40.3% in group ˂7 days, compared with 50% of female, and female present 15.3% in group ˃14 days compared with 20.6% of male. Conclusions: Height, weight, FLR size and gender could be the variables that most constantly influence both daily growths, the interstage increase and the standardized FLR before the second stage.